Molecular Identification of Dominant Microbes in Kola nut (Cola nitida) - Garuba, T.; Ajala, Fatimoh Adeola; Olahan, Ganiyu Shittu; Lateef, Azeez Adebola (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Kola nut is an important dehiscent fruit but its supply fails to meet the demand due to limitations such as inadequate post-harvest practices leading to spoilage during transportation and storage. Identification of microbial contaminants is a necessary step in reducing the loss. Hence, this work aimed at characterizing the genome of dominant fungus and bacteria associated with kola nut (Cola nitida). Samples of kola nuts were collected from Oje and Oja-oba markets in Ibadan, Nigeria. Isolates were extracted from the lesion region of the samples using the standard method. Macro-morphological and micro-morphological observations of the pure culture of the isolates were conducted. After genomic DNA extraction of fungal and bacterial isolates, Polymerase Chain Reaction (PCR) was carried out using Internal Transcribed Sequence (ITS 1 and ITS 4) and 27F primers for fungal and bacterial genome respectively. Sanger sequencing of the purified DNA fragments was conducted utilizing the Nimagen, BrilliantDye™ Terminator Cycle Sequencing Kit V3.1, BRD3-100/1000. Molecular Evolutionary Genetics Analysis (MEGA version 6) was used for phylogenetic analysis. The result revealed that one fungus and two bacteria were associated with kola nuts. The fungal isolate showed 100% identity with Aspergillus wentii from the National Center for Biotechnology Information data base. The fungus showed a good relationship with A. dimorphicus and A. europaeus. The two bacterial isolates were also identified through the phylogenic analysis as Bacillus cereus and B. subtilis. B. cereus is closely related to B. thuringiensis. This research provides background information on the Kola nut microbial contaminant. Keywords: Bacteria, Contaminant, Fungus, Identification, Primers, Sequencing